The apostolic fathers ... by the late J.B. Lightfoot - Clement I, Pope.; Ignatius Saint, Bishop of Antioch, d. ca. 110.; Polycarp Saint, Bishop of Smyrna.; Lightfoot, Joseph Barber (Macmillan, 1889)
pt. I. S. Clement of Rome. A revised text with introductions, notes, dissertations and translations. 1890. 2 v.--pt. II. S. Ignatius. S. Polycarp. Revised texts, with introduction notes, dissertations, and translations. 1885. 3 v.